Transformation of Madrasah Learning Methods: Adapting Modern Pedagogies within the Context of Islamic Educational Tradition - Sugianto, Sugianto; Sahrodin, Sahrodin; Wahyudi, Sahidin; Hidayat, Rahmad; Utama, Esen Pramudya (Westscience Press, 2025)
This study examines the transformation of teaching methods in Islamic schools (madrasahs) by integrating traditional approaches emphasizing classical text instruction and memorization with modern technological tools. The research is motivated by the need to align madrasah education with the digital era while preserving the Islamic values that form the institution’s core identity. Employing a qualitative case study design, the study explores the experiences of teachers, principals, students, and education administrators. Data were collected through interviews, classroom observations, and document analysis, and subsequently analyzed thematically using triangulation to ensure validity and reliability. Findings indicate that the incorporation of multimedia resources, e-learning platforms, and digital applications enhances students’ engagement and comprehension of Islamic subjects while promoting active participation in the learning process. Nevertheless, challenges such as limited digital infrastructure and teachers’ readiness to use technology remain significant barriers. The results support the constructivist perspectives of Piaget and Vygotsky, as well as Garrison et al.’s Community of Inquiry framework, all of which emphasize interaction and collaboration as central to effective learning. Practically, the study suggests greater investment in digital infrastructure, continuous professional development for teachers, and the design of integrated curricula that harmonize modern knowledge with Islamic values. These insights are expected to inform policymakers and educational practitioners in optimizing hybrid learning models within madrasah settings.